Elementos que influyen en la decisión de invertir. - Rengel Espinoza, Andre Joshue (My University, 2019)
The feasibility study of a project is crucial for a natural or legal person to make the decision to invest in the production of goods or services that generate profitability, in our environment there are many entrepreneurs who make investments empirically for the creation of their Business. In this research work we will analyze the elements that influence the decision to invest in a project through field research and bibliography to establish the determinants of the feasibility of the investment. The study was carried out through a literature review and through the research tool of the survey of 20 businessmen from the city of Machala.
El estudio de factibilidad de un proyecto es determinante para que una persona natural o jurídica tome la decisión de invertir en la producción de bienes o servicios que le generen rentabilidad, en nuestro entorno existen muchos emprendedores que realizan inversiones de manera empírica para la creación de sus empresas. En este trabajo de investigación se analizará los elementos que influyen en la decisión de invertir en un proyecto mediante investigación de campo y bibliográfica para establecer los determinantes de la factibilidad de la inversión. El estudio se realizó mediante revisión bibliográfica y mediante la herramienta de investigación de la encuesta a 20 empresarios de la ciudad de Machala.
Keywords: INVERSIÓN; ESPONSABILIDAD SOCIAL; FACTIBILIDAD; DECISIONES; PROCESOS